Epidermal cysts of the head and neck: a clinicopathologic analysis of 112 cases. - Li, Y.; Wang, S.; Zhang, R. (European Journal of Pediatric Dermatology, 2021)
Background. Epidermal cysts are common benign intradermal or subcutaneous tumors that can also occur in oral mucosa and internal organs. The clinical presentation is variable, so the diagnosis of epidermal cysts needs histopathological confirmation. Methods. A retrospective case-series study of histologically proven epidermal cysts of the head and neck presenting from January 2017 to January 2020 at the Department of Dermatology, the Third Affiliated Hospital of Soochow University in China was carried out. Clinical details, including age, gender, sites and histopathological results, were noted. Results. The highest incidence of epidermal cysts was observed in the age group of 31–40 years (20.5%, 23/112) and the most commonly affected site of the head was the ear (15.4%, 10/65). Histopathological findings included rupture of epidermal cysts with giant cell reactions (15 cases) and infections (28 cases). Conclusion. Epidermal cysts are common benign lesions of hair-bearing skin. An epidermal punctum is a hallmark of the clinical diagnosis; however, epidermal cysts can have unusual presentations. Early diagnosis and treatment are needed to avoid cosmetic damage, since epidermal cysts are mostly located in the head region.